(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of the Ciek Duo Tigo Dance extracurricular at SMP Negeri 18 Padang by following the steps that already exist in the extracurricular program. This activity is driven by students’ interest and talent in dancing as a place to develop their potential. This type of research uses a descriptive qualitative method. The informants consist of the dance extracurricular instructor and the vice principal of student affairs at SMP Negeri 18 Padang. Data was collected through observation, interviews, and documentation, and then described through reduction, presentation, and drawing conclusions using source triangulation. The research results show that the implementation went well. Planning included program preparation, member recruitment, scheduling, as well as facilities and infrastructure. The execution took place over five meetings, namely introduction, review and memorization of movements, technique improvement, floor pattern practice, and performance simulation carried out based on aspects of wiraga, wirama, and wirasa, which showed significant improvement. This activity concluded with a performance at the farewell event for 9th-grade students and retired teachers of SMP Negeri 18 Padang on May 29, 2026. The challenges faced included limited practice space and inconsistent student attendance, but the activity still ran optimally as a platform for talent development.